Binding of the chemokine CXCL12α to its natural extracellular matrix ligand heparan sulfate enables myoblast adhesion and facilitates cell motility. (April 2017) - Thakar, Dhruv; Dalonneau, Fabien; Migliorini, Elisa; Lortat-Jacob, Hugues; Boturyn, Didier; Albiges-Rizo, Corinne; Coche-Guerente, Liliane; Picart, Catherine; Richter, Ralf P.
Abstract: The chemokine CXCL12α is a potent chemoattractant that guides the migration of muscle precursor cells (myoblasts) during myogenesis and muscle regeneration. To study how the molecular presentation of chemokines influences myoblast adhesion and motility, we designed multifunctional biomimetic surfaces as a tuneable signalling platform that enabled the response of myoblasts to selected extracellular cues to be studied in a well-defined environment. Using this platform, we demonstrate that CXCL12α, when presented by its natural extracellular matrix ligand heparan sulfate (HS), enables the adhesion and spreading of myoblasts and facilitates their active migration. In contrast, myoblasts also adhered and spread on CXCL12α that was quasi-irreversibly surface-bound in the absence of HS, but were essentially immotile. Moreover, co-presentation of the cyclic RGD peptide as integrin ligand along with HS-bound CXCL12α led to enhanced spreading and motility, in a way that indicates cooperation between CXCR4 (the CXCL12α receptor) and integrins (the RGD receptors). Our findings reveal the critical role of HS in CXCL12α induced myoblast adhesion and migration. The biomimetic surfaces developed here hold promise for mechanistic studies of cellular responses to different presentations of biomolecules. They may be broadly applicable for dissecting the signalling pathways underlying receptor cross-talks, and thus may guide the development of novel biomaterials that promote highly specific cellular responses.